2018
DOI: 10.4317/jced.54933
|View full text |Cite
|
Sign up to set email alerts
|

Condylar response to large mandibular advancement combined with maxillary impaction and counterclockwise rotation: A computed tomographic study

Abstract: BackgroundThis study aims to analyze the effectiveness of cone-beam computed tomography (CBCT) in the evaluation of the condylar position, angulation and intercondylar distance and assess the changes in these parameters before and after bimaxillary surgery, preformed with the critical movments of Le Fort I osteotomy (for impaction of the maxilla and conterclockwise rotation of the upper occlusal plane) and Bilateral Sagittal Split Osteotomy (BSSO) for mandibular advancement (> 8mm).Material and MethodsTwenty c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The role of condylar rotation after mandibular advancement has been discussed controversially. Although some authors described that the use of fixation, including positional screws [ 13 ] and miniplates [ 58 , 59 ] for BSSO provoked inward condylar rotation and medial condylar displacement, others reported that in BSSO for mandibular advancement the fixation with miniplates [ 16 ] had no significant effect on the corresponding condylar changes. However, it is known that mandibular advancement usually produces greater condylar displacement if the anterior osteotomy gap is forcefully closed with rigid fixation [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of condylar rotation after mandibular advancement has been discussed controversially. Although some authors described that the use of fixation, including positional screws [ 13 ] and miniplates [ 58 , 59 ] for BSSO provoked inward condylar rotation and medial condylar displacement, others reported that in BSSO for mandibular advancement the fixation with miniplates [ 16 ] had no significant effect on the corresponding condylar changes. However, it is known that mandibular advancement usually produces greater condylar displacement if the anterior osteotomy gap is forcefully closed with rigid fixation [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of CBCT has been reported for determining changes in condylar position after bilateral sagittal split ramus osteotomy (BSSO) for mandibular advancement, without [9][10][11][12][13][14] or with [15][16][17][18] a LeFort I osteotomy. According to these studies, condylar displacement after mandibular advancement surgery is variable.…”
Section: Introductionmentioning
confidence: 99%
“…Vale et al, aiming to analyze the effectiveness of CBCT in evaluating the condylar position, angulation, and intercondylar distance and to assess the changes in these parameters before and after bimaxillary surgery in class II patients, showed that the surgery did not significantly change the mandibular condyles. However, they tended to migrate inferiorly and posteriorly [ 32 ]. These findings are equivalent to the current study’s findings for patients with class II malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the variables were measured according to the methods defined by Vale et al [ 23 ]. All measurements were performed by a single authors follows:…”
Section: Methodsmentioning
confidence: 99%
“… CBCT image evaluation: ( a ) midpoints of reference; ( b ) Frankfort horizontal plane; ( c ) midsagittal plane; ( d1 ) intercondylar distance; ( d2 ) condylar angulation in the axial plane; ( d3 ) condylar angulation in the frontal plane; ( d4 ) condylar angulation in the sagittal plane; ( d5 ) condylar position in the sagittal plane. Adapted from Vale et al [ 23 ]. …”
Section: Figurementioning
confidence: 99%